A Decade Review of the Art of Inspection and Monitoring Technologies for Long-Distance Oil and Gas Pipelines in Permafrost Areas - Pengchao Chen; Rui Li; Guangming Jia; Hao Lan; Kuan Fu; Xiaoben Liu (Energies, 2023)
Long-distance oil and gas pipelines buried in permafrost areas will inevitably encounter typical geological disasters, such as frost heave and thaw settlement and sliding, which easily cause pipeline displacement, bending, or deformation. When there are certain defects in the pipeline, additional complex, external stress will further lead to the failure of the pipeline or weld and can even lead to serious accidents such as pipeline leakage, pipe burst, or fracture. This paper introduces in detail the typical defects and risks of buried pipelines in permafrost areas and summarizes the in-line inspection technologies, off-line inspection technologies, and integrated monitoring systems for pipelines in the pipeline industry. Regarding pipelines in permafrost areas, in-line inspection methods may be employed. These include magnetic flux leakage, electromagnetic eddy current, ultrasonic, IMU, and electromagnetic acoustic transducer inspections. Off-line inspection is also one of the important means of inspecting a pipeline in a permafrost area. Indirect inspection is combined with verification by direct inspection to check and evaluate the integrity of the anticorrosive coating and the effectiveness of the cathodic protection for the pipeline. Meanwhile, considering the external environment of a pipeline in a permafrost area, a monitoring system should be developed and established. This paper discusses and projects the future development of related technologies, which provides reference for the construction and operation of pipelines in permafrost areas.